Plasmonic enhancement of coherence in random lasers - Wan Zakiah Wan Ismail; Vo T.P.; Stark P.; Coutts D.; Goldys E.; Dawes J. (Institute of Electrical and Electronics Engineers Inc., 2024)
We observe the enhancement of coherence due to localized surface plasmon resonance in random laser from gold nanoparticles. Higher coherence is obtained for random lasers with gold nanoparticles than with alumina nanoparticles.